CO2 activation of char from argan nutshells pyrolysis a preliminary study - Afailal, Zainab; Gil-lalaguna, Noemí; Macías, Robert J.; Gonzalo, Alberto; Arauzo, Jesus; Luis Sanchez, Jose (Jornada de Jóvenes Investigadores del I3A, 2021)
CO2 physical activation was performed to produce activated carbons from pyrolysis char. The process was fed by char produced in the pyrolysis of argan nutshells. This unexplored feedstock is a residue of argan oil production. This preliminary study showed that the activated carbons obtained in this process are characterized by a large surface area and a great capacity to retain contaminants.